Aluminum oxide and copper oxide nanodiesel fuel properties and usage in a compression ignition engine. (1st January 2016) - Gumus, Soner; Ozcan, Hakan; Ozbey, Mustafa; Topaloglu, Bahattin
Highlights: The synthesis and physicochemical properties of nanodiesel including CuO and Al2 O3 nanoparticles were investigated. The combustion performance of nanodiesel in a diesel engine was also investigated. Nano particle addition were improved the flash point temperature and cetane index of diesel. The addition of Al2 O3 and CuO decreases BSFC but also reduces NO x emissions. Abstract: This study deals with an experimental work that aims to examine the effects of nanoparticles added to diesel fuels. Nanodiesel fuels were prepared by adding aluminum oxide and copper oxide nanoparticles. These nanoparticles were blended with diesel fuel in varying mass fractions by the means of a mechanical homogenizer and an ultrasonicator. Physicochemical properties of nanodiesels were measured and compared with neat diesel fuel. Their stability characteristics were analyzed under static conditions. The effects of the additive nanoparticles on the engine performance and emissions were also investigated. The results showed that the stability of nanodiesel can be increased by regulating pH and using dispersant. The storage and combustion characteristics were also improved by adding nanoparticles. The engine test results indicated that the nanodiesel in terms of engine performance efficiency and environmentally friendly emissions could be recognized as the potential candidates in diesel engines.